The Relationship Self-Efficacy and Treatment Compliance in Chronic Kidney Failure Patients at Hospital - Pinondang Hotria Siregar; Melva Epy Mardiana Manurung; Dewi Hutagaol (Information Technology and Science (ITScience), 2026)
Chronic Kidney Disease (CKD) is a disease that occurs due to complete or partial kidney damage. The impact of this kidney failure is the inability to filter kidneys, so treatment methods include hemodialysis and fluid restriction. Objective: This study aimed to determine the relationship between self-efficacy and medication adherence in patients with chronic kidney disease (CKD). This study used a quantitative descriptive cross-sectional study design. The sampling technique used a total sampling of 33 respondents using Spearman's analysis. Results: The self-efficacy of CKD patients at Djasamen Saragih Regional Hospital with HD durations of <1 year was shown to be moderate, 21.2% (7) had high self-efficacy, and 12.1% (4) had low self-efficacy. The majority of CKD patients undergoing HD durations of <1 year (97%) were compliant with medication, while 3% (1) were non-compliant. The 2-tailed significance value (Significant) is 0.853 > 0.05, thus it can be concluded that there is no relationship between self-efficacy and treatment adherence in chronic kidney disease (CKD) patients at Djasamen Saragih Regional General Hospital, Pematang Siantar. Healthcare workers are expected to continue providing counseling to improve the self-efficacy of chronic kidney disease (CKD) patients and to encourage families to continue providing support, motivation, and communication to patients undergoing hemodialysis.